Предмет: Математика, автор: дарья762

4 , не получается , помогите

Приложения:

Ответы

Автор ответа: FerryRum
0
(1 frac{1}{2} +2 frac{2}{3} +3 frac{3}{4} )*3 frac{4}{5} *(14-15 frac{1}{8} :2 frac{1}{5} )= \  \ =( frac{3}{2} + frac{8}{3} + frac{15}{4} )* frac{19}{5} *( frac{14}{1} - frac{121}{8} : frac{11}{5} )= \  \ = frac{(3*6+8*4+15*3)}{12} * frac{19}{5} *( frac{14}{1} - frac{121}{8} * frac{5}{11} )= \  \=  frac{95}{12} * frac{19}{5} *( frac{14}{1} - frac{55}{8} )= frac{19*19}{12} * frac{(14*8-55)}{8} = \  \ = frac{361}{12} * frac{57}{8} = frac{20577}{96} =214 frac{11}{32}
Похожие вопросы
Предмет: Математика, автор: рпопороп